ID 283 – EEG markers of motor activity in physiological aging and Alzheimer's disease mouse models. Issue 3 (March 2016) - Lopez, S.; Del Percio, C.; Bastlund, J.F.; Forloni, G.; Frasca, A.; Bentivoglio, M.; Fabene, P.F.; Bertini, G.; Kelley, J.; Dix, S.; Richardson, J.C.; Drinkenburg, W.; et al.
Abstract : Objectives: In the framework of IMI PharmaCog project (Grant Agreement n°115009), we evaluated whether spectral electroencephalographic (EEG) markers of motor activity change across aging in wild type (WT) mice and in transgenic models of AD. Methods: All animal studies were carried out ethically (86/609/EEC). EEG data were recorded from bipolar fronto-parietal electrode in 85 WT mice, 22 PDAPP, and 33 TASTPM mice. Artifact-free EEG segments during wake active and passive state (no sleep) were used as input for EEG power density analysis. Results: Statistical results ( p  < 0.05) showed: (1) higher 6–8 Hz power density during active state in the old (20–24 months) than the middle-aged (12–14 months) and young (4.5–6 months) WT mice, (2) higher 8–10 Hz power density during the active state in the young than in the middle-aged and old WT mice, (3) lower 2–6 Hz power density during the passive state in the TASTPM and PDAPP than in the WT mice, and (4) lower 8–10 Hz power density during the active state in the TASTPM and PDAPP than in the WT mice. Conclusions: EEG markers of motor activity are useful to unveil neurophysiological mechanisms of cortical neural synchronization characterizing the physiological and pathological aging in mice.